Academics' Conceptions of Teaching Sustainability. (31st March 2015) - Wyatt, Meg
Abstract: Over the last decade, a growing number of universities have committed to ensuring that sustainability is integral to higher education with the intent of preparing eco-literate graduates who can make positive contributions to the sustainability of the environment. With particular consideration for the increasingly internationalised teaching environment of many higher education institutions, this study sought to explore how academics' conceptions of teaching sustainability might differ across disciplines. This study builds upon the seminal work of Reid and Petocz (2006 ), Cotton, Bailey, Warren, and Bissell (2009 ) and Cotton, Warren, Maiboroda, and Bailey (2007 ), who explored the views of academics across a range of disciplines not traditionally associated with sustainability. This study extends their research by specifically identifying academics from a variety of disciplines who might be considered experts in the field of sustainability. The study takes a constructivist view of 'conceptions' that are developed through one's experiences, beliefs and interactions with community. The theoretical framing also identifies pedagogical approaches recommended in the fields of sustainability and intercultural education, and establishes eco-literacy and environmental ethics as integral to one's conceptions of sustainability. This research applied a multi case-study approach, including open-ended interview questions with participants from four different faculties of Monash University, namely: Science; Business and Economics; Education; and Medicine, Nursing and Health Sciences. All four participants were selected on the basis of the synopsis of the unit they taught overtly stating that sustainability-related content was included in the syllabus, and thus might be defined as experts in the teaching of sustainability. The data was analysed using descriptive followed by interpretative coding, which ultimately identified six different components that might contribute to the participants' conceptions about their teaching. These components included: discipline; conceptions of sustainability; ethical position; pedagogical approach; approach to intercultural education; and approach to eco-literacy. The findings of the study conclude that there were likely to be disciplinary differences in the academics' conceptions of teaching sustainability. While there was no evidence of a disciplinary link to the academics' understanding of what sustainability is, the research did appear to support a correlation between an academic's previous education and their ethical position. Furthermore, the current discipline of their unit appeared to strongly reflect their pedagogical approach to teaching sustainability. The research also highlights that, while there are clearly some innovative teaching strategies being utilised, there is room for more transformational learning to be included in syllabus design. Additionally, as the number of unit outlines that overtly referred to sustainability was surprisingly low, and not all sustainability-related units seemed to demonstrate a comprehensive approach to the teaching of eco-literacy, questions are raised about whether all students are actually engaging in sustainability education as signatories of the Talloires Declaration have pledged. The significant contribution of this study is represented by its implications for the development of curriculum and syllabus design in the field of sustainability education. Having highlighted the potential disciplinary differences between approaches to teaching sustainability, a range of stakeholders, including university faculties and individual academics, can review how sustainability education is taught in their curriculum and address areas that require greater attention to ensure students receive a comprehensive exposure to the skills and knowledge required to develop eco-literacy.